Latin America and the Caribbean Code Against Cancer 1st Edition: Medical interventions including hormone replacement therapy and cancer screening - Baena, A (2023)
Prostate, breast, colorectal, cervical, and lung cancers are the leading cause of cancer in Latin America and the Caribbean (LAC) accounting for nearly 50% of cancer cases and cancer deaths in the region. Following the IARC Code Against Cancer methodology, a group of Latin American experts evaluated the evidence on several medical interventions to reduce cancer incidence and mortality considering the cancer burden in the region. A recommendation to limit the use of HRT was issued based on the risk associated to develop breast, endometrial, and ovarian cancer and on growing concerns related to the over-the-counter and without prescription sales, which in turn bias estimations on current use in LAC. In alignment with WHO breast and cervical cancer initiatives, biennial screening by clinical breast examination (performed by trained health professionals) from the age of 40 years and biennial screening by mammography from the age of 50 years to 74, as well as cervical screening by HPV testing (either self-sampling or provider-sampling) every 5–10 years for women aged 30–64 years, were recommended. The steadily increasing rates of colorectal cancer in LAC also led to recommend colorectal screening by occult blood testing every two years or by endoscopic examination of the colorectum every 10 years for both men and women aged 50–74 years. After evaluating the evidence, the experts decided not to issue recommendations for prostate and lung cancer screening; while there was insufficient evidence on prostate cancer mortality reduction by prostate-specific antigen (PSA) testing, there was evidence of mortality reduction by low-dose computed tomography (LDCT) targeting high-risk individuals (mainly heavy and/or long-term smokers) but not individuals with average risk to whom recommendations of this Code are directed. Finally, the group of experts adapted the gathered evidence to develop a competency-based online microlearning program for building cancer prevention capacity of primary care health professionals.